Advanced analytics for green and sustainable economic development : supply chain models and financial technologies - Luo, Zongwei, 1971- (Hershey, PA : Business Science Reference, 2012)
'This book focuses on the development of innovative techniques and tools that answer urgent questions in the global trend of sustainable economic development, providing researchers and business managers with a valuable resource for the development of green business and application of low carbon practices'--Provided by publisher.
Includes bibliographical references (p. 231-245) and index.
Keywords: Sustainable development -- Environmental aspects; Sustainable development -- Finance; Economic development -- Environmental aspects; Industries -- Environmental aspects